Whole genome insights into genetic diversity, introgression, and adaptation of Yunnan indigenous cattle of Southwestern China - Xiwen Guan; Weixuan Xiang; Kaixing Qu; Zulfiqar Ahmed; Jianyong Liu; Ming Cai; Jicai Zhang; Ningbo Chen; Chuzhao Lei; Bizhi Huang (BMC Genomics)
Abstract Background Yunnan Province, located in Southwestern China, the intricate geography, variable climate, and abundant vegetation of the region have collectively contributed to shaping the distinctive germplasm characteristics observed in Yunnan indigenous cattle through prolonged domestication. The different breeds of Yunnan cattle exhibit distinct advantageous characteristics and traits, which are an important source of genetic variation because they might carry alleles that enable them to adapt to local environment and tough feeding conditions. However, a comprehensive genomic landscape of genetic resources has yet to be delineated. Results Herein, we employed 140 whole-genome sequencing data from Yunnan indigenous cattle across eight breeds to elucidate their genetic diversity and population structure. Utilizing both uniparental and biparental markers, we elucidated the intricate genetic composition of Yunnan indigenous cattle, which is closely correlated with the geographic environment. A predominant East Asian indicine ancestry which gradually diminishes towards the north. The analysis revealed a high genetic diversity among populations and a low-to-moderate inbreeding coefficient, underscoring the rich genetic reservoir of Yunnan cattle breeds. Additionally, gene flow between Yunnan indicine and wild Bos species in and around Yunnan was verified, highlighting localized introgression from Yunnan Gayal as a critical factor in the successful adaptation of Yunnan indicine cattle to the local hot and humid environments. Conclusions Our findings established the SNPs database for facilitating resource conservation and selective breeding. Moreover, these valuable insights into the genomic diversity and adaptive history of Yunnan indigenous cattle breeds contribute significantly to our understanding of their evolutionary dynamics and offer a foundation for future genetic improvement and conservation strategies.